KEPUASAN MENUJU SINERGI: BAGAIMANA APLIKASI FINTECH MENGOPTIMALKAN EFISIENSI TRANSAKSIONAL DALAM EKONOMI DIGITAL PASCA-PANDEMI - Umi Lailatul Muniroh; Boy Ghozy Fadholi; Suprayitno; Mahdha Nafilata Aulia Az-Zulfa; Diana Pramudya Wardhani (Journal AK-99, 2026)
This study aims to analyze the transformation mechanism of fintech user satisfaction into transactional efficiency within the post-pandemic digital economy ecosystem in Indonesia. Specifically, it examines the mediating roles of digital trust and digital synergy, as well as the moderating effect of digital literacy on the relationship between user satisfaction and transactional efficiency. Integrating Expectation-Confirmation Theory and Service-Dominant Logic, this quantitative study involved 420 active fintech users in Indonesia. Research instruments were adapted from internationally validated studies and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4 with 5,000-subsample bootstrapping procedures. Results indicate that user satisfaction significantly drives digital trust formation (β = 0.542, p < 0.001) and digital synergy (β = 0.485, p < 0.001). The pathway to transactional efficiency is indirect, strongly mediated by the synergy between users and the platform ecosystem. Digital literacy strengthens the impact of satisfaction on efficiency optimization (β = 0.185, p = 0.002). This research introduces the "Digital Synergy" construct as a bridge between psychological responses and technical operational outcomes a dimension previously overlooked in fintech management literature. The proposed "Satisfaction-to-Synergy" model offers strategic guidance for fintech providers in emerging markets to optimize economic value through user collaboration and digital feature excellence.